Policing Policy 05-2014: Command Order - (:unkn) unknown (My University, 2014)
In this command order, the Jail Division Commander of Sutter County Sheriff's Office dictates that the office will no longer hold inmates or intakes based solely on Immigration and Customs Enforcement (ICE) holds or detainers.
Keywords: Sanctuary Policies; DHS Form I-247; Miranda-Olivares v. Clackamas County; 8 CFR § 287.7